Sustainability issues of various denim washing methods - Khan, Md. Khalilur Rahman (Array, 2021)
Denim washing is increasingly joining the list of indispensable processes of meeting the demands of the world"s shifting fashion industry. Other than this, there is a rising trend in the sustainability perception among both producers and customers in the modern world. However, denim washing is considered to have direct impacts on the environment because of its chemical discharge and many other pollutants emitted during the process which affect water supplies. In the process, the denim industry encounters challenges at every level. Therefore, there is need for studying sustainable problems associated with denim washing. The unseen soul of the denim industry is technology, as nothing can be transformed without technological advancement. Sustainability problems of conventional washing have been addressed in this paper (i.e. pp spray washing, bleaching washing, stone washing, sand blasting etc.). Furthermore, the paper describes how sustainability can be achieved through the most recent washing techniques, such as laser, waterjet, nanobubble, ozone, NoStone, potassium permanganate alternatives etc. The introduction of new technologies has triggered a dramatic shift in the denim washing industry in terms of water usage, electricity and chemicals as well as improved quality. Consequently, it is undoubtful that the recent technologies in denim washing are crucial in making the industry sustainable. Moreover, the paper describes the idea of digitally printed denim and the available software for measuring sustainability in the process of denim washing.